2004
DOI: 10.1111/j.1471-0307.2004.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Cheese technology

Abstract: Cheese is a highly nutritious food with many diverse flavours and textures. It can be used as a snack or as part of a dish or prepackaged convenience food. The diversity of cheese is due to an increasing knowledge of the technology of cheesemaking, and the biochemistry and microbiology of cheese ripening. Professor Pat Fox's research career over the past 40 years has contributed to our understanding of cheese technology, biochemistry and microbiology. This paper highlights Pat Fox's contributions in the area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 33 publications
1
65
0
3
Order By: Relevance
“…At the start of ripening, lactose is quickly metabolized into lactate. This lactate is an imperative precursor for the production of lactic acid through a series of metabolic reactions and transformations including microbial processes, oxidationreduction reactions and racemisation [10,23]. Murtazaet al [2] also found the increase in lactic acid concentration in Cheddar cheese during the first few weeks of ripening owing to the use of residual lactose trapped in the curd.…”
Section: Lactic Acidmentioning
confidence: 95%
See 2 more Smart Citations
“…At the start of ripening, lactose is quickly metabolized into lactate. This lactate is an imperative precursor for the production of lactic acid through a series of metabolic reactions and transformations including microbial processes, oxidationreduction reactions and racemisation [10,23]. Murtazaet al [2] also found the increase in lactic acid concentration in Cheddar cheese during the first few weeks of ripening owing to the use of residual lactose trapped in the curd.…”
Section: Lactic Acidmentioning
confidence: 95%
“…However, lactose decreased significantly (p<0.01) from 0.15±0.005 to 0.06±0.004% resulting in significant drop of pH and increase in acidity from 5.34±0.021 to 5.19±0.024 and 0.90±0.007 to 0.96±0.006%, respectively. The fermentation of lactose resulted in fall of pH and rise in acidity because various metabolic reactions and transformations including glycolysis occur during cheese ripening [1,10]. Among these reactions, the conversion of lactose into lactate and other metabolic products by lactic acid producing bacteria is imperative and manipulate the concentration and production rate of acidification [20].…”
Section: Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes can find many industrial applications, namely: 1) in the textile industry after textile blenching (Costa et al, 2002a), 2) in the food industry after cold pasteurization of milk (Farkye, 2004), 3) coupled with oxidases, prevention of the inactivation of the oxidases by the deleterious action of a high concentration of peroxide (Fernández-Lafuente et al, 1998) and 4) coupled with oxidases, prevention of side reactions caused by the H2O2 that can destroy the target product (Schoevaart and Kieboom, 2001). It is worth noting that application of catalase reduces 48% of the energy consumption, 83% of the chemical costs, 50% of the water consumption and 33% of the processing time (Eberhardt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cheese ripening occurs as a result of various microbiological, biochemical, and metabolic processes (Farkye, 2004). Proteolysis, which occurs for as long as the cheese ripening, is the most complicated and significant biochemical process (Sousa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%